In/visible Recoveries: Display events, Stigma and Spirituality in a Therapeutic Community in Northern Mexico - Sharp, Ethan (Implicit religion, 2019)
Based on ethnographic research in Northern Mexico, this article describes the efforts of men within a therapeutic community closely tied to Alcoholics Anonymous (AA) to manage perceptions of AA recovery pathways, and to define for themselves and the larger public the nature of the spirituality that they acquired in recovery. Through an analysis informed by discourse studies and linguistic anthropology, the article shows that through discourse and symbolic actions in public display events, the men reinforced a belief in the effectiveness of AA recovery pathways by affirming their stigmatized identities as "addicts," and by framing experiences such as rejection by family, an arrest or an encounter with death as possibilities for demonstrating honesty and authenticity, and for developing a sense of spirituality and the confidence needed to do the work of recovery. The men's spirituality did not rely on any kind of consistent religious or spiritual practice; rather, it involved recognizing God as a force in their lives and remaining open to new discoveries and insights.